Konstribusi Pembina Keagamaan dalam Mengembangkan Karakter Bela Negara Di Batalyon Yonif 100/Ps - Jannah, Miftahul; Abrianto, Danny (Yayasan Rahmat Islamiyah, 2023)
A sense of nationalism, patriotism, and love for the homeland is an attitude of defending the country which is the main element with the development of technological developments should be able to facilitate the younger generation in forming an attitude of defending the country, but the fact is quite the opposite, with the development of technology the younger generation today even fades the attitude of defending the country, even though defending the country is a jihad group which if done wholeheartedly and humanity also upholds the rights of religious people Therefore, this research is important to know the role of religious coaches in developing the character of defending the state which makes this apparatus with the character of defending the state, only it does not conflict with their respective religions. With this, religious leaders become a very important contribution for TNI members to continue to carry out their worship even though they are in a state of defending the country, such as praying during war, and so on.